Enhancing combustion and emission characteristics of CI engines through atomization and fuel–air mixing using non-circular orifices: A path towards sustainable biodiesel utilization - Mukesh Yadav; Ashok Kumar Yadav; Aqueel Ahmad (Green Technologies and Sustainability)
Environmental concerns, energy security and requirements motivate the researcher to consider biodiesel as a renewable and sustainable substitute for compression ignition (CI) engines in comparison to commercial diesel. Fuel modification and spray process are important parameters for engine combustion, performance and emissions of CI engines. The fundamental physics of spray atomization processes from various injectors, emphasizing recent research findings. Biodiesel sprays demonstrate faster penetration with a narrower spray plume angle and larger droplet sizes when compared to diesel. The build-up of a fuel-rich mixture in the combustion chamber can lead to reduced performance and increased emissions of carbon monoxide (CO), hydrocarbon (HC), particulate matter (PM), and nitrogen oxide (NOx). Moreover, the use of alternative fuels, such as biodiesel based on vegetable oils, animal fats and algae, often falls short of meeting desired performance standards due to their lower heating (calorific) value and high rheological properties such as viscosity, density and surface tension. This can result in poor atomization, uneven fuel–air mixture and alter spray penetration leading to incomplete combustion. Therefore, researchers are looking for techniques and modifications that can enhance the spray characteristics and atomization of fuel. This article evaluates the impact of non-circular orifices on atomization and fuel–air mixing and how they affect the performance and emissions of CI engines. The study analyzes the advantages and disadvantages of injection parameters and fuel modification, considering their respective effects on performance and emissions. This research found that non-circular orifices, especially elliptical orifices, showed superior atomization and fuel–air mixing compared to circular orifices. Furthermore, the simultaneous implementation of non-circular orifices and fuel modification techniques exhibited the potential for enhancing thermal efficiency and decreasing emissions in CI engines.